2D Material Based Thin‐Film Nanocomposite Membranes for Water Treatment. Issue 10 (22nd February 2021) - Yang, Jindi; Li, Zhikao; Wang, Zhuyuan; Yuan, Shi; Li, Yang; Zhao, Wang; Zhang, Xiwang
Abstract: Membrane‐based separation technologies are essential in the fields of desalination and wastewater treatment. 2D material based thin‐film nanocomposite (2D‐M‐TFN) membranes are emerging technology that combines 2D nanomaterials and conventional thin‐film composite membranes. It has great potential to further improve the efficiency of the membrane separation process. Although extensive studies are reported, 2D‐M‐TFN membranes for water treatment are not systemically reviewed. This work gives an intensive summary of this emerging technology. The function, mechanisms, and common characteristics of various 2D materials in the 2D‐M‐TFN membrane are first summarized and compared. An in‐depth discussion of different types of 2D‐M‐TFN membranes is then conducted, followed by the discussions on the challenges and opportunities. Abstract : In this paper, the recent research in the field of 2D material based thin‐film nanocomposites (TFN) membranes is systemically reviewed. The function, mass transport mechanism, and common characteristics of various 2D materials in the TFN membranes are summarized and compared. An in‐depth discussion of different types of 2D material based TFN membranes is then conducted.